Metaphor in school teaching of textsTowards a new vision (مجلة إحالات, 2026)
This article seeks to propose a theoretical and applied conception of teaching metaphorical discourse inthe unit of teaching and reading texts at the upper level of secondary education, a concept drawn from the conceptual perspective of metaphor.Although this conception, which was behind Mark Johnson and George Lakoff, was based primarily on everyday language, we expanded it, following some of their later conceptions, to include literary discourse.Our goal in establishing the teaching of metaphor on thisperspective is to transcend the traditional perceptions that consider metaphor as a verbal transmission andthen focus on the transmitted and transmitted from it in operations based on inventory and classification without looking at this metaphor as a form of reorganizing reality and its things, and it is a door to understanding this Indeed, they are innovative.